Mythological Image in Olonkho of the North-Eastern Yakut Tradition: Sacred Tree - Pavlova, Olga Ksenofontovna (Journal of History Culture and Art Research, 2018)
The article discusses the problem of studying the North-Eastern tradition of the Yakut epic. This tradition is part of the Northern regional tradition of the Yakuts. At the moment, the problem of studying the Northern regional tradition remains open. The study was based on the works of P. Ergun, V.N. Toporov, L.V. Dmitrieva, I.V. Pukhov, N.V. Emel’yanov, L.N. Semenova and others. The images and semantics of the sacred tree in the Olonkho of the North-Eastern tradition are considered in detail. This image is characteristic for the 8 texts of the 14 considered Olonkho from momskiy, verkhoyanskiy, abyiskiy and srednekolymskiy districts or Sakha (Yakutia) Republic local traditions. In Olonkho texts of studied tradition the sacred larch image is widespread. As the researchers note, the sacred larch image is the most archaic. Carried out a comparative analysis of the sacred tree in Olonkho from three traditions (Vilyui, Central and North-Eastern). The sacred tree descriptions in the three traditions had their own regional differences. As a result of sacred tree semantics comparison in Olonkho of three traditions had been revealed the following. In the Central tradition, the sacred tree does not reach the Upper and the Lower worlds. In the Vilyui tradition, the tree penetrates through the Middle world and reaches the Upper world, becomes the horse standing for the Supreme deity Ürüng Aÿý toÿon ‘White Creator Lord’. In Olonkho of the studied tradition the top of the sacred tree goes to the Upper world and roots penetrate deep into the Lower world. In the middle world the tree Ál Lúk Mas appears as a center of the world and a sacred place. In the Lower world the sacred tree appears as a hook for the things of its Lord Arsán Tôlaya. The main results of the work allows to suggest that the sacred tree semantics in the Olonkho of this tradition is more interesting and distinctive from the Olonkho of other regional traditions.